Pengembangan Media Monopoli Kecerdasan Emosi (MONKESI) dalam Bimbingan Klasikal Dengan Teknik Problem Based Learning Tentang Kecerdasan Emosi - Rohmaniati, Aghni; Danni Rosada, Ulfa; Hartanto, Dody; Fauziah, Mufied (Universitas PGRI Palembang, 2025)
Higher levels of emotional intelligence trigger more intense responses to mood, including negative reactions that can increase distress in less favorable conditions. This research aims to produce appropriate Monopoly on Emotional Intelligence (MONKESI) media based on expert assessments of materials, media and BK services, as well as testing its effectiveness in increasing emotional intelligence through classical guidance based on problem based learning. This research uses the R&D method with the Borg and Gall model up to the sixth stage, namely the trial stage. The research instruments include scale validation test assessments, material experts, media and services. Data were analyzed descriptively qualitatively based on expert suggestions and comments and quantitatively using percentages of expert test results. The research results show expert validation as follows: material experts gave 84 points, media experts 95.45 points, and service experts 94.4 points. Monopoly Media for Emotional Intelligence (MONKESI) was declared suitable for use by students and BK teachers. Trials using SPSS showed an average pretest score of 63.8 and posttest 74.3, with a sig value of 0.000 < 0.05, which proves a significant increase in the emotional intelligence of class VII C MTs Serba Bakti students through classical guidance services based on problem-based learning.